The impacts of Ukraine war on supply chain management (Russia and Ukraine) - Lee, Xin Yin (Nanyang Technological University, 2023)
Russia’s invasion of Ukraine on 24 February 2022, marks the escalation of the ongoing Russia-Ukraine War that started in 2014. It is currently one of the most pressing global issues as the conflict has become a political and economical issue that has had far-reaching implications on global supply chain management. Although the conflict receives widespread media coverage, there is a noticeable shortage of academic research regarding how the war impacts the supply chain management of cargo owners trading with respective nations. This report focuses on Russia and Ukraine specifically with the other two reports written by Alda “Choo” and “Seng” Hong Yi focusing on the European Union and China respectively. To address this gap, this study delved into the multifaceted impact of the Russia-Ukraine War on supply chain management, with a specific focus on the Political and Economical impact on Cargo Owners trading with Russia and Ukraine. Interviews and surveys were conducted, revealing the Political impact with factors such as increased policies and sanctions and how it affected the operations and SCM of cargo owners and also the rise in shadow fleets. Economical impact included factors such as disruption of trade routes, alternative sources, increased cost and prices, depreciation of currencies, trade sanctions and also the rise in fuel fraud cases. All the impact of these factors on cargo owners are stipulated in this report and practical recommendations are given to help cargo owners reposition themselves in case of future political events of a similar nature. Each recommendation is associated with a risk or challenge faced by cargo owners. Some examples of recommendations given are using hedging techniques, long term contracts and strategic stockpiling to mitigate Price Risk, diversifying the business and sourcing for alternatives to mitigate Disruptions in Trade Routes and others written in the Recommendations chapter. In conclusion, this study sheds light on the complex and drastic impact of the Russia-Ukraine war on the SCM of cargo owners. It also offers valuable insights into the strategies and adaptations necessary to navigate the evolving geopolitical landscape.